Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review: 45



Work Step by Step

$(a^{\frac{1}{2}} \times a^{-2})^{3}$ =$(a^{\frac{1}{2}-2})^{3}$ =$(a^{\frac{1-2(2)}{2}})^{3}$ =$(a^{\frac{1-4}{2}})^{3}$ =$(a^{\frac{-3}{2}})^{3}$ =$a^{-\frac{9}{2}}$ =$\frac{1}{a^{\frac{9}{2}}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.